2019
DOI: 10.1007/s40618-019-01077-8
|View full text |Cite
|
Sign up to set email alerts
|

The treatment with pasireotide in Cushing’s disease: effect of long-term treatment on clinical picture and metabolic profile and management of adverse events in the experience of a single center

Abstract: Purposes Pasireotide is the first medical therapy officially approved for adult patients with Cushing's disease (CD) experiencing failure of pituitary surgery or not candidates for surgery. The current study aimed at investigating pasireotide effects on clinical picture and metabolic profile in patients enrolled in the phase III CSOM230B2305 trial at Naples center. In addition, the current study focused on safety issues encountered during the study, detailing the management of the different adverse events asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Today, drug-based therapies represent the gold standard to address abnormal lipid. However, the therapeutic approach has a major limitation, side effects, which in most cases could lead to nausea and vomiting for patients . This has encouraged scientists to search for novel routes to deal with it, and dietary intervention comes up to be a better choice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, drug-based therapies represent the gold standard to address abnormal lipid. However, the therapeutic approach has a major limitation, side effects, which in most cases could lead to nausea and vomiting for patients . This has encouraged scientists to search for novel routes to deal with it, and dietary intervention comes up to be a better choice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic approach has a major limitation, side effects, which in most cases could lead to nausea and vomiting for patients. 36 This has encouraged scientists to search for novel routes to deal with it, and dietary intervention comes up to be a better choice. Related to the present data, the research of galacto-oligosaccharides in treating lipid metabolic disorders has been reported widely.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Pasireotide, as subcutaneous injection, is formulated as three different immediate-release ampoules, containing 300, 600, and 900 µg doses, with suggestion of a maximum total daily dose of 1,800 µg. Pasireotide has been extensively evaluated in human clinical studies, leading to a large amount of evidence about its efficacy and safety in CD treatment (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The first classical formulation of pasireotide was subcutaneously administered in a twice-daily schedule, with two doses, 600 and 900 µg.…”
Section: Pasireotidementioning
confidence: 99%
“…Treatment discontinuation occurred in 84 (51.8%) patients, because of AEs in 26 (16%) and lack of efficacy in 37 (22.8%) patients (18). Following the first two main clinical trials, additional clinical studies focused on long-term response to pasireotide treatment (21)(22)(23)(24)(25)(28)(29)(30). In an extension study to 24 months of the phase II trial (clinicaltrials.gov code: NCT00171951) on 19 CD patients, considering the 18 patients included in the primary efficacy analysis, pasireotide treatment at doses ranging from 300 to 1,800 µg/day demonstrated mUC normalization in four (22.2%) patients and a reduction in mUC, defined as lower than that at core study baseline, but not within normal range, in additional six (33.3%) patients after 6 months of treatment, with a total success rate of 55.5%.…”
Section: Pasireotidementioning
confidence: 99%
See 1 more Smart Citation